Perspectivas do meio-fio: entre os direitos sociais e as histórias de vida da população em situação de rua na região do Vale do Ribeira-SP - Miyahara, Heloísa Sayumi (2017)
The thesis establishes an analytical comparison between the list of legally assured rights and the life histories of homeless population in Vale do Ribeira Region, investigating and identifying gaps and alternatives for overcoming them. The specific objectives were: To draw a qualitative profile of the population in homeless situation in Vale do Ribeira-SP, to identify in life histories the possibilities of interaction with public policies and to characterize the service offered to the homeless population in Region. This is a qualitative research, motivated by recent discussion about the importance of a proper methodology for investigating the social condition of the homeless people. We worked with a methodology to rescue the life history intertwined with aspects of social rights. The data analysis related theoretical categories with the empirical collection of material. We delimited as research universe the 14 municipalities that make up the area covered by Regional Office of Assistance and Social Development – DRADS – Vale do Ribeira interviewing two Groups of Subjects (Group I – Technicians and Group II – Homeless People)